The Influence of Occupational Safety, Occupational Health, and Work Discipline on Employee Performance - Nur Alamsyah; Kuswandi Kuswandi; Sri Rahayu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of occupational safety, occupational health, and work discipline on employee performance at PT. SLI. The research method used is quantitative with saturated sampling technique, where the entire population of 70 employees is used as a sample. Data collection was carried out through questionnaires, while data analysis used multiple linear regression. The results of the study indicate that occupational safety, occupational health, and work discipline partially have a positive and significant influence on employee performance. Simultaneously, the three variables also contribute positively and significantly to employee performance, with a determination coefficient value of 89.1%. This confirms that the factors of safety, health, and work discipline play a very important role in improving performance in this company engaged in the transportation and processing of B3 waste. This study is expected to provide practical contributions to human resource management at PT. SLI and become a reference for similar research in other industrial sectors.